The effects of oxidizer-to-fuel ratio on some characteristics of a silver iodide pyrotechnic for cloud seeding - Jose, Wilfredo L. (1976)
With constant silver iodide content the oxidizer-to-fuel ratio of the pyrotechnic formulation is varied from 0.5 to 8 by weight. The temperature of reaction and the burning rate decrease as the ration is increased. The average smoke particle sizes are large for low rations and smaller but essentially constant for high ratios with a minimum exhibited between 3 and 2.5 The maximum threshold temperature of ice crystal formation is likewise between the ratios of 3 and 3.5.
The result show that the average particle size is dependent on burning rate and the temperature of reaction with the effect of burning rate and temperature of reaction with the effect of burning rate more pronounced. The threshold temperature of ice crystal formation is dependent on the burning rate, temperature of reaction, and average smoke particle size. These however, are not complete dependence since the nuclei surface structure maybe a controlling factor on the threshold temperature. The study shows that the best ratio is between 3 and 3.5 for the particular formulation used.
Mimeographed.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Rain-making.